Some properties for Beurling algebras - Mahmoodi, A. (Methods of Functional Analysis and Topology, 2009)
Let G be a locally compact group and let ω be a weight function on G. In this paper, among other things, we show that the Beurling algebra L^1(G,ω) is super-amenable if and only if G is finite and it is biprojective if and only if G is compact.